Well-being from Work in the Pacific Island Countries - World Bank (Washington, DC, 2014)
In the Pacific island countries, which are small and far from world markets, labor mobility represents the most significant and substantial opportunity for overcoming geographic constraints on employment. This report presents a brief overview of employment challenges in small Pacific island countries and recommendations for addressing them. The report contributes to an ongoing World Bank analytical program examining the linkages between employment and well-being around the world, begun with the World Development Report 2013: jobs. Discussion in this report relates to Pacific island states, with populations of significantly less than one million, including Solomon Islands, Vanuatu, Samoa, Tonga, Tuvalu, Kiribati, Republic of Marshall Islands, Federated States of Micronesia, and Palau. Economic growth and diversification has been very limited in these countries because of the barriers imposed by smallness and distance, and these barriers will not be quickly overcome. This report provides five priorities that are likely to be broadly applicable to the unique group of countries. First, stakeholders' expectations about the trajectory of development will need to be realistic. Second, the volume of international labor mobility should be increased through the erosion of regulatory barriers and investment in transferable human capital. Third, governments can work to harness the positive potential of urbanization through investment in improved rural services, connective infrastructure, and improved urban administration. Fourth, productive public spending can be used as a mechanism for creating new employment opportunities. Finally, policies can ensure that natural resource industries provide a sustainable source of employment creation.